Non-fullerene acceptor organic photovoltaics with intrinsic operational lifetimes over 30 years - Li, Yongxi; Huang, Xiaheng; Ding, Kan; Sheriff, Hafiz K. M.; Ye, Long; Liu, Haoran; Li, Chang-Zhi; Ade, Harald; Forrest, Stephen R. (Nature communications, 2021)
Organic photovoltaic cells (OPVs) have the potential of becoming a productive renewable energy technology if the requirements of low cost, high efficiency and prolonged lifetime are simultaneously fulfilled. So far, the remaining unfulfilled promise of this technology is its inadequate operational lifetime. Here, we demonstrate that the instability of NFA solar cells arises primarily from chemical changes at organic/inorganic interfaces bounding the bulk heterojunction active region. Encapsulated devices stabilized by additional protective buffer layers as well as the integration of a simple solution processed ultraviolet filtering layer, maintain 94% of their initial efficiency under simulated, 1 sun intensity, AM1.5 G irradiation for 1900 hours at 55 °C. Accelerated aging is also induced by exposure of light illumination intensities up to 27 suns, and operation temperatures as high as 65 °C. An extrapolated intrinsic lifetime of > 5.6 × 10 4 h is obtained, which is equivalent to 30 years outdoor exposure. Through development of non-fullerene acceptors, OPVs have reached efficiencies of 18%, yet the inadequate operational lifetime still poses a challenge for the commercialisation. Here, the authors investigate the origin of instability of NFA solar cells, and propose some strategies to mitigate this issue.